2013
DOI: 10.2134/jeq2013.05.0167
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Fertilizer Nitrogen Rates and Yield-Scaled Global Warming Potential in Drill Seeded Rice

Abstract: Drill seeded rice ( L.) is the dominant rice cultivation practice in the United States. Although drill seeded systems can lead to significant CH and NO emissions due to anaerobic and aerobic soil conditions, the relationship between high-yielding management practices, particularly fertilizer N management, and total global warming potential (GWP) remains unclear. We conducted three field experiments in California and Arkansas to test the hypothesis that by optimizing grain yield through N management, the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 53 publications
14
58
0
Order By: Relevance
“…The proportion of CH 4 emitted following flood release in this study, however, was similar to emissions ranging from 10.5% from CLXL745 to 16% from a semi-dwarf, pure-line cultivar observed by Rogers et al [30]. Post-flood CH 4 release has been observed in numerous previous studies ranging from 3 to 20% of total area-scaled emissions [30,32,51,54,56,70,74]. While the magnitude of post-flood-release CH 4 emissions differs among various treatments, it has become apparent that CH 4 has the potential to accumulate in saturated soils and be released as the soil dries and macropores become accessible for gas transport.…”
Section: Seasonal Methane Emissionssupporting
confidence: 85%
See 3 more Smart Citations
“…The proportion of CH 4 emitted following flood release in this study, however, was similar to emissions ranging from 10.5% from CLXL745 to 16% from a semi-dwarf, pure-line cultivar observed by Rogers et al [30]. Post-flood CH 4 release has been observed in numerous previous studies ranging from 3 to 20% of total area-scaled emissions [30,32,51,54,56,70,74]. While the magnitude of post-flood-release CH 4 emissions differs among various treatments, it has become apparent that CH 4 has the potential to accumulate in saturated soils and be released as the soil dries and macropores become accessible for gas transport.…”
Section: Seasonal Methane Emissionssupporting
confidence: 85%
“…Fluxes incrementally decreased again at 6 and 7 DAFR (2.65 and 0.56 mg CH 4 -C m -2 h -1 , respectively). The post-flood-release pulse of CH 4 that occurred in this study has been observed in previous studies [30,32,48,49,53,54,55,56], usually occurring from 3 to 6 DAFR, and is generally attributed to the release of CH 4 from soil pores as they drain and allow transport of previously entrapped gases.…”
Section: Methane Fluxes Following Flood Releasesupporting
confidence: 78%
See 2 more Smart Citations
“…Increased nitrogen fertilization rate enhanced net GWP and GHGI due to increased N 2 O emissions and CO 2 emissions associated with manufacture, transport, and application of nitrogen fertilizers, regardless of cropping systems and methods of calculations [3,7,21,33,42,55]. In a meta-analysis of 12 experiments, Sainju [56], after accounting for all sources and sinks of CO 2 emissions, reported that net GWP decreased from 0 to ≤45 kg N ha…”
Section: Nitrogen Fertilizationmentioning
confidence: 99%